Intranuclear inclusions of polyQ-expanded ATXN1 sequester RNA molecules - Gkekas, Ioannis; Vagiona, Aimilia-Christina; Pechlivanis, Nikolaos; Kastrinaki, Georgia; Pliatsika, Katerina; Iben, Sebastian; Xanthopoulos, Konstantinos; Psomopoulos, Fotis E.; Andrade-Navarro, Miguel A.; Petrakis, Spyros (Frontiers in Molecular Neuroscience, 2023)
Spinocerebellar ataxia type 1 (SCA1) is an autosomal dominant neurodegenerative disease caused by a trinucleotide (CAG) repeat expansion in the ATXN1 gene. It is characterized by the presence of polyglutamine (polyQ) intranuclear inclusion bodies (IIBs) within affected neurons. In order to investigate the impact of polyQ IIBs in SCA1 pathogenesis, we generated a novel protein aggregation model by inducible overexpression of the mutant ATXN1(Q82) isoform in human neuroblastoma SH-SY5Y cells. Moreover, we developed a simple and reproducible protocol for the efficient isolation of insoluble IIBs. Biophysical characterization showed that polyQ IIBs are enriched in RNA molecules which were further identified by next-generation sequencing. Finally, a protein interaction network analysis indicated that sequestration of essential RNA transcripts within ATXN1(Q82) IIBs may affect the ribosome resulting in error-prone protein synthesis and global proteome instability. These findings provide novel insights into the molecular pathogenesis of SCA1, highlighting the role of polyQ IIBs and their impact on critical cellular processes.